Causal inference for statistics, social, and biomedical sciences: An introduction - Imbens, Guido W.; Rubin, Donald B. (New York Cambridge University Press, 2015)
ost questions in social and biomedical sciences are causal in nature: what would happen to individuals, or to groups, if part of their environment were changed? In this groundbreaking text, two world renowned experts present statistical methods for studying such questions. This book starts with the notion of potential outcomes, each corresponding to the outcome that would be realized if a subject were exposed to a particular treatment or regime.